In Vitro Synergy of Isavuconazole Combined With Colistin Against Common Candida Species - Schwarz, Patrick; Nikolskiy, Ilya; Bidaud, Anne-Laure; Sommer, Frank; Bange, Gert; Dannaoui, Eric (Frontiers in Cellular and Infection Microbiology, 2022)
Interactions of isavuconazole and colistin were evaluated against 57 common Candida strains belonging to the species Candida albicans (n = 10), Candida glabrata (n = 10), Candida kefyr (n = 8), Candida krusei (n = 10), Candida parapsilosis (n = 9), and Candida tropicalis (n = 10) by a broth microdilution checkerboard technique based on the European Committee on Antimicrobial Susceptibility Testing (EUCAST) reference methodology for antifungal susceptibility testing. Results were analyzed with the fractional inhibitory concentration index and by the response surface analysis. Interpretation by the fractional inhibitory concentration index showed synergy for 50%, 80%, 90%, and 90% of the C. kefyr, C. krusei, C. glabrata, and C. tropicalis strains, respectively. Combination of isavuconazole with colistin against C. albicans and C. parapsilosis exhibited only indifference for 100% and 90% of the strains, respectively. The results were confirmed by response surface analysis for all species except for C. glabrata, for which an indifferent interaction was found for the majority of strains. Antagonistic interaction was never seen regardless of the interpretation model was used.